PERANCANGAN USER INTERFACE PADA ECOMERCCE WEBSITE CV YANTO KONVEKSI DENGAN PENDEKATAN USER-CENTERED DESIGN DAN EVALUASI SYSTEM USABILITY SCALE - Rezayanti Novia Putrika Dewi; Habib Waliyudin, Ridwan; Lahema, Yehezkiel (Jurnal Intent: Jurnal Industri dan Teknologi Terpadu, 2025)
CV Yanto Konveksi is a micro, small, and medium enterprise (MSME) providing garment manufacturing services in Tangerang Regency, marketing its products independently through conventional methods. Its marketing activities primarily rely on printed media (banners/flyers) and verbal promotion. Furthermore, the ordering process is still carried out in a conventional manner, either by visiting the business location or placing orders via telephone. This approach has proven less effective in operating the business and has resulted in limited market exposure. In line with the shift in consumer behaviour towards the use of technology, it is essential for the business to adopt an adaptive approach to ensure its continuity and growth. Based on this need, designing a user interface for an e-commerce website can facilitate potential customers in placing orders, support the company’s marketing efforts, and provide convenience to consumers when ordering products. This study employs the User-Centered Design method, in which the design is developed based on the buyers’ needs. The resulting design was evaluated using the System Usability Scale method with 50 respondents, achieving a score of 85.25 with a “Best Imaginable” rating, indicating that the website interface is of excellent quality and successfully meets user needs.